SEU Mitigation for SRAM FPGAs: A comparison via Probabilistic Model Checking - Pereira, Viny Cesar; Júnior, Valdivino Alexandre de Santiago; Manea, Silvio (Anais do Workshop de Testes e Tolerância a Falhas (WTF), 2017)
Although there are several Single-Event Upset (SEU) mitigation techniques for SRAM-based Field Programmable Gate Arrays (FPGAs), comparisons are still necessary regarding dependability analyzes of these techniques. Most of these assessments analyze the techniques after design and implementation in FPGA which may be too costly. Stochastic/Probabilistic analysis allow to obtain results in the early stages of design. In this paper, we compare three of these strategies, Scrubbing, Triple Modular Redundancy (TMR), and Hamming code, via Probabilistic Model Checking. Results show that TMR allows upsets to accumulate and must be combined with Error Correction Codes (ECCs), such as Hamming, and that the Scrubbing interval directly affects reliability while safety is more related to the coverage rate.